Elephant (Loxodonta africana) home ranges in Sabi Sand Reserve and Kruger National Park: a five-year satellite tracking study - Thomas B; Holland J; Minot E (PLoS ONE, 2008)
During a five-year GPS satellite tracking study in Sabi Sand Reserve (SSR) and Kruger National Park (KNP) we monitored the daily movements of an elephant cow (Loxodonta africana) from September 2003 to August 2008. The study animal was confirmed to be part of a group of seven elephants therefore her position is representative of the matriarchal group. We found that the study animal did not use habitat randomly and confirmed strong seasonal fidelity to its summer and winter five-year home ranges. The cow's summer home range was in KNP in an area more than four times that of her SSR winter home range. She exhibited clear park habitation with up to three visits per year travelling via a well-defined northern or southern corridor. There was a positive correlation between the daily distance the elephant walked and minimum daily temperature and the elephant was significantly closer to rivers and artificial waterholes than would be expected if it were moving randomly in KNP and SSR. Transect lines established through the home ranges were surveyed to further understand the fine scale of the landscape and vegetation representative of the home ranges.
Funding: We gratefully acknowledge the financial support of the Institute of Natural Resources, Massey University. The funder had no role in study design, data collection and analysis, decision to publish, or preparation of the manuscript.
Keywords: Elephant; Loxodonta africana; Habitat; Satellite tracking; Fields of Research::300000 Agricultural, Veterinary and Environmental Sciences::300800 Environmental Science::300802 Wildlife and habitat management